Words and Things - ABRAHAMYAN, ASHOT (Bulletin of Yerevan University B: Philology, 2021)
The main strategic modes of linguistic representation of reality – nomination and deixis – are embodied by nominative and deictic words, nominative words including common names and proper names. The three types of words, distinguished in this way, are often mentioned as means of identification of the referent and are simply enumerated, without substantiating the existence of precisely these types. Meanwhile, the analysis proves that they constitute a regular system, parts of which can be defined and compared with each other, using quantitative characteristics. It is owing to the existence of these three semantic-functional types of words that full semantic coverage of reality and full referential identification of speech components become possible.
Keywords: significat, denotation, referent, nomination, deixis, proper name, common name, deictic word